The religious and social significance of self-assigned religious affiliation in England and Wales: comparing Christian, Muslim and religiously-unaffiliated adolescent males. (1st November 2014) - Francis, Leslie J.; Robbins, Mandy
Abstract: This study examines the religious and social significance of self-assigned religious affiliation among young people in England and Wales by investigating religious beliefs and the connection between religion and matters of public concern among a sample of 547 adolescent males between 16 and 18 years of age, distinguishing between three religious groups: Christian, Muslim, and non-affiliated. First, the analysis identified eight themes concerning religious beliefs: the Bible, the Qur'an, Jesus, Muhammad, Jesus and justice, Muhammed and justice, experiencing God, and the theology of religions. Second, the analysis identified six themes concerning the connection between religion and matters of public concern: religion and personal life, religion and public life, religion and the state, social rights, the rights of women and children, and sex and morality. The data highlighted some areas of commonality and some areas of strong divergence between the three groups, demonstrating how the religious and social significance of self-assigned religious affiliation hold salience in some areas rather than others.